Preparing Teacher Leaders for English Language Learners in Rural Settings - Coady, Maria R; Lopez, Mark Preston; Marichal, Nidza; Heffington, Deon (Theory & Practice in Rural Education, 2019)
The number of English language learners (ELs) across the United States continues to grow, particularly in rural and new destination settings. However, educators remain un- and under-prepared for working with ELs nationally. This article provides findings from a study of one teacher leader professional development program in a rural school district that sought to prepare educators for ELs. We describe the professional development program and the rural context of the district. Findings from this study derive from an online survey of participants. Data reveal that rural educators seek to acquire skills and strategies that go beyond the classroom setting and that enable them to connect with EL families. They also believe that teacher leaders of ELs demonstrate compassion and build social-emotional support networks for themselves as professionals, as well as with EL families.